Role of subjective norms in shaping entrepreneurial intentions among Students in Finland - Mia, Shahin (My University, 2025)
This thesis explores the role of subjective norms in shaping entrepreneurial intentions among students in Finland, with a particular focus on how the subjective norms interact with behavioral, experiential, and demographic variables. This study examines both direct and indirect influences of subjective norms, emphasizing the mediating roles of attitudes toward entrepreneurship and perceived behavioral control guided by the Theory of Planned Behavior (TPB). Using quantitative analysis techniques such as regression analysis, mediation analysis, and ANOVA, the study discovers that subjective norms significantly impact entrepreneurial intentions, primarily through behavioral mediators. Attitudes toward entrepreneurship emerged as the strongest influencing factor. Perceived behavioral control also showed a significant impact. Interestingly, while the presence of entrepreneurs in individual’s network had a positive effect on subjective norms, exposure to highly successful entrepreneurs exposed a negative association. Demographic factors such as gender, age, and education level were found to have no significant effect. The study contributes to entrepreneurial intention literature by refining the understanding of how social influences operate through internal cognitive processes. It offers practical recommendations for educators, policymakers, and institutional leaders, urging them to prioritize confidence-building, mentorship, and inclusive entrepreneurship programs. By addressing both theoretical and practical dimensions, this research supports the development of a more nuanced and effective approach to fostering entrepreneurship in higher education.
Keywords: Subjective Norms, Entrepreneurial Intentions, Theory of Planned Behavior, Attitudes towards entrepreneurship, Perceived Behavioral Control, University student